2012
DOI: 10.1016/j.sbspro.2012.09.909
|View full text |Cite
|
Sign up to set email alerts
|

Turbo-roundabouts vs Roundabouts Performance Level

Abstract: In this paper the performance level of basic turbo-roundabouts and double-lane roundabouts are compared. Cowan’s M3\ud headway distribution was chosen to take into account bunched vehicles moving along each circulating lane; the Hagring\ud model was adopted to evaluate entry capacity both at turbo-roundabout and at double-lane roundabout.\ud The comparative analysis was performed evaluating operational performances in terms of delay suffered by users entering the\ud intersection.\ud Results of the analyses sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…However, the critical headway and the follow-up headway being stochastically distributed cannot be considered as constant values, but each of them should be represented by a distribution of a set of values. Moreover, when capacity models based on the gap acceptance theory are used, analyst should specify the probability distribution of headways between vehicles in each major stream (Giuffrè et al, 2012a).…”
Section: Calculation Of Roundabout Operationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the critical headway and the follow-up headway being stochastically distributed cannot be considered as constant values, but each of them should be represented by a distribution of a set of values. Moreover, when capacity models based on the gap acceptance theory are used, analyst should specify the probability distribution of headways between vehicles in each major stream (Giuffrè et al, 2012a).…”
Section: Calculation Of Roundabout Operationsmentioning
confidence: 99%
“…This is why Cowan's M3 headway distribution explicitly accounts for the number of bunched vehicles through the proportion of free vehicles expressed by the ϕ parameter. Some bunching models to estimate ϕ formulated by several authors have been collected by Giuffrè et al (2012a) and Akçelik (2007).…”
Section: Gap Acceptance Capacity Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In urban context, turbo roundabouts showed good performance considering simultaneous presence of pedestrians and vehicles [19,20]. Giuffrè et al [21] found that the performance of turbo roundabouts highly depended on traffic situations. Turbo roundabouts performed better on major roads with higher demands.…”
Section: Introductionmentioning
confidence: 99%
“…When major-stream vehicles are moving very close together, minor-stream vehicles can enter the intersection when the gap after the last vehicle of the platoon meets or exceeds the critical gap (Tanner [20]). In the case of turbo roundabouts, where different entering modes are coexisting, application of capacity models assuming the same arrival headway distribution for each circulating stream has to be preferred (see Giuffrè, Granà, S. Marino [21]). …”
Section: Introduction To the Operational Analysis Of Roundaboutsmentioning
confidence: 99%